2008
DOI: 10.1037/0893-164x.22.1.12
|View full text |Cite
|
Sign up to set email alerts
|

The role of drug use in a conceptual model of intimate partner violence in men and women arrested for domestic violence.

Abstract: In a previous study, alcohol problems in perpetrators and their partners contributed directly and indirectly to intimate partner violence (IPV), even after including other correlates of violence in the model (G. L. Stuart et al., 2006). The present study extends these findings by examining the role of illicit drug use. We recruited 271 men and 135 women arrested for IPV and used structural equation modeling to examine the data. Results showed that drug use, as reported by the perpetrators, was a stronger predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
174
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(195 citation statements)
references
References 80 publications
18
174
2
1
Order By: Relevance
“…This is consistent with the findings of previous studies 20,25,26 which showed that smoking, alcohol consumption, and using other substances of abuse were strongly associated with IPV. Substance abuse, including smoking and alcohol consumption, may be directly responsible for IPV by affecting cognition, reducing self-control, perpetuating aggression and may also induce stress and unhappiness in relationships, thereby, further increasing the risk of violence and conflict.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is consistent with the findings of previous studies 20,25,26 which showed that smoking, alcohol consumption, and using other substances of abuse were strongly associated with IPV. Substance abuse, including smoking and alcohol consumption, may be directly responsible for IPV by affecting cognition, reducing self-control, perpetuating aggression and may also induce stress and unhappiness in relationships, thereby, further increasing the risk of violence and conflict.…”
Section: Discussionsupporting
confidence: 83%
“…Substance abuse, including smoking and alcohol consumption, may be directly responsible for IPV by affecting cognition, reducing self-control, perpetuating aggression and may also induce stress and unhappiness in relationships, thereby, further increasing the risk of violence and conflict. 26 This study has some limitations. It was conducted in selective family practice clinics which may have underestimated the results due to underreporting.…”
Section: Discussionmentioning
confidence: 99%
“…La tasa de agresores que presentan problemas de abuso o dependencia alcohólica puede oscilar entre el 50% y el 60% (Echeburúa, Fernández-Montalvo, y Amor, 2003;Fernández-Montalvo, Echeburúa, y Amor, 2005; Fernández-Montalvo y Klostermann y Fals-Stewart, 2006;Stuart, O´Farrell, y Temple, 2009). En el caso de otro tipo de drogas ilegales, los datos varían en las diferentes investigaciones pero, como media, en torno al 20% de los hombres agresores presenta un consumo abusivo de drogas (Fals-Stewart, Golden, y Schumacher, 2003; Fernández-Montalvo y Moore et al, 2008;Stuart et al, 2008). En este sentido, la mayor parte de los estudios se han centrado en el consumo de cocaína y de cannabis.…”
Section: Introductionunclassified
“…Smokers high in trait anger have greater mood difficulties during abstinence and are more vulnerable to early relapse than smokers with low trait anger. Research with other stimulant users suggests a role for anger, aggression and other emotion regulation factors in cocaine and amphetamine consumers [15][16][17] . These findings implicate trait anger to be associated with poor emotional regulation and vulnerability to substance misuse and relapse.…”
Section: Introductionmentioning
confidence: 99%